Assessing accessibility of sexual reproductive health services among adolescents and young people living with HIV/AIDS in Kenya - Nyang’echi, Edna N.; Osero, Justus O. S. (International Journal Of Community Medicine And Public Health, 2024)
Background: Sexual and reproductive health rights (SRHR) are fundamental human rights enshrined in national, regional, and international laws and agreements. This study aimed to determine the accessibility of SRHR services among young people living with HIV/AIDS in Kenya. Methods: The study was a cross-sectional study involving a sample of 224 adolescents and young people from Kenya. The study used both qualitative and quantitative methods of data collection and analysis. Before the study commenced, approvals were acquired from the Kenyatta University ethics and review committee, the National Commission for Science, Technology, and Innovation, County Governments, and selected county and sub-county health facilities in Kenya. Results: About 68.2% of adolescents and young people (AYP) living with HIV/AIDS accessed SRH services with a significant difference in proportion between study counties (Nairobi city and Homabay counties) in Kenya (χ2=20.553; df=2; p<0.0001). Nevertheless, 33% of them reported that there were challenges that affected access to SRHR services and the unavailability of some services. Therefore, there is a need to ensure enough and constant supply of commodities and supplies for comprehensive care services. Conclusions: The study showed a statistically significant difference in the proportion of AYP living with HIV/AIDS who accessed SRH services in the study counties of Nairobi city and Homabay.